A Case Study Of Perusahaan Otomobil Kedua Sdn. Bhd's Corporate Strategy - Pawanchik, Zambri (2009)
This case study gives details on Perodua as a whole - the company's background and history, its vision and mission, its organizational structure and functions and its milestones and achievements throughout its 15 years. Perodua is the current market leader in the Malaysian automotive industry and is continously growing to even greater heights.